The 21st century accounting career from the perspective of the Malaysian university students - Ghani, Erlane K.; Said, Jamaliah; Mohd Nasir, Noraini; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2008)
Using questionnaire setting, this study examines the perception of the Malaysian public university students on the accounting career in Malaysia. This study seeks to identify the respondents’ preferred accounting career, their career exposure, the factors perceived to be important for an accountant and the acquisition qualities of an accountant. The results of this study provide interesting responses from the respondents. More respondents prefer to become a public accountant rather than holding a management post. The respondents obtained their career exposure mostly from the professional accounting bodies and the factors perceived to be most important in an accountant are work performance and self confidence. Salary is also one of the factors perceived to be important for an accountant. The respondents also perceived the essential qualities of an accountant are acquired through education. The results of this study provide insights to the bodies of accounting profession, employers and academics on the nature and relative importance of the factors deemed important for the accounting students in their employment decision and their preferences to employment opportunities.